ETNOBOTANI TUMBUHAN PANGAN SUKU DAYAK SEBERUANG KECAMATAN TEMPUNAK KALIMANTAN BARAT - Kusuma Wardhani, Hilda Aqua; Ningsih, Verunika (Prodi Biologi Universitas PGRI Ronggolawe, 2025)
This study examined the diversity and utilization of food plants by the Dayak Seberuang community in Suka Jaya Village, Tempunak District, Kalimantan Barat. This research used an ethnobotanical approach that aimed to understand the relationship between the Dayak Seberuang people and the plants in Suka Jaya Village. The data collected included data on food plant species and community knowledge about the management and utilization of plant species as food. Data collection was carried out by direct observation, interviews and documentation. The determination of respondents used was the snowball sampling method. The results showed that 53 species of food plants were found to be utilized by the Dayak Seberuang community of Suka Jaya Village, Tempunak District, Kalimantan Barat as food. The most commonly found food plants were species from the Cucurbitaceae family (6 species). Some types of food plants that were identical to the typical food of the Dayak Seberuang tribe were Brassica juncea (ensabi), Solanum ferox (terung asam), Smilax barbata (remudang), Ficus variegata Blume (kedadai), Hevea brasiliensis (karit), and Dillenia indica (simpur).